Carbon-mediated epitaxy of SiGe virtual substrates on Si(001). (4th October 2018) - Schmidt, Jan; Tetzlaff, Dominic; Wietler, Tobias F; Osten, H Jörg
Abstract: We report on the effect of carbon sub-monolayer deposition on the growth of thin Si1− x Ge x layers on Si(001) substrates. The deposition of a C sub-monolayer prior to full crystallization of the Si1− x Ge x layer supresses the otherwise energetically favorable Stranksi–Krastanov growth mode upon annealing and yields a smooth surface at high degrees of relaxation for a layer thickness below 100 nm for different Ge contents. The samples are characterized with respect to the surface reconstruction, surface morphology, strain state and defect structure. We discuss the exceptional number of stacking faults in the Si1− x Ge x layer and propose an explanation for the phenomenon. Finally, we present a process flow to grow smooth, undoped and almost fully relaxed Si1− x Ge x layers at very low thickness (<100 nm) for virtual substrate applications.